Education Reward for Teacher: Implementation Strategy to Improve Teacher’ Performance - Sri Sarjana (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2016)
Abstract Reward for teacher became one of the ways to improve teachers’ performance for the development of national education. It is an appreciation for teachers based on merit or the excellent performance, given both individually and institutionally in the form of material or appreciation. A competent teachers have the ability, skill, and attitude of work in accordance with established standards. The purposed of this study is to analyze the effect of reward on teachers in creating performance through the optimization of creativity, innovation development and competence. The data were analyzed through triangulation model of transformation that combines qualitative and quantitative methods. The findings indicate that teachers’ reward model that able to create performance through increasing the creativity, innovation, and competence. Furthermore, this study is expected to build awareness of the ministry of education in improving the quality of national education systems including the expansion of rewards for teachers who have great working performance in creativity, innovation and competence.Abstrak Penghargaan bagi guru menjadi salah satu tuntutan dalam upaya peningkatan prestasi kerja untuk pengembangan kualitas pendidikan nasional. Penghargaan guru merupakan bentuk apresiasi terhadap guru berdasarkan prestasi atau kinerja unggul yang diberikan baik perorangan maupun lembaga dalam bentuk materil maupun lisan. Guru yang kompeten memiliki kemampuan, ketrampilan maupun sikap kerja sesuai dengan standar yang ditetapkan. Tujuan penelitian ini untuk menganalisis pengaruh penghargaan guru dalam rangka menciptakan prestasi kerja melalui optimalisasi kreativitas, pengembangan inovasi dan peningkatan kompetensi. Teknik analisis data menggunakan model triangulasi transformasi yang memadukan metode kualitatif dan kuantitatif. Temuan dalam penelitian ini mengintegrasikan model penghargaan guru yang mampu menciptakan prestasi kerja melalui upaya meningkatkan kreativitas, inovasi, dan kompetensi. Lebih lanjut, penelitian ini mengharapkan kementerian pendidikan nasional lebih berperan aktif dalam meningkatkan kualitas sistem pendidikan nasional diantaranya melalui perluasan pemberian penghargaan bagi guru yang memiliki keunggulan dalam kreativitas, inovasi dan kompetensi. How to Cite : Sarjana, S. Khayati, N. Warini, L. (2016). Education Reward for Teacher: Implementation Strategy to Improve Teacher’ Performance. TARBIYA: Journal of Education in Muslim Society, 3(2), 205-217. doi:10.15408/tjems.v3i2.4390. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i2.4390